Metacognitive strategies: Effects on metacognitive awareness, self-efficacy, reading performance and motivation - Cequeña, Maria B. (Animo Repository, 2009)
This study investigated the effects of metacognitive strategies on the freshman high school students' metacognitive awareness, self-efficacy, reading performance and motivation. It also attempted to find out if there is a significant relationship between and among metacognitive awareness, self-efficacy, reading performance and motivation. The respondents comprised of two experimental classes who were taught metacognitive strategies by two teachers who had undergone similar orientation and training on metacognitive strategies such as think aloud and Caverly, Nicholson and Mandeville's (1995) Predict, Locate, Add and Note (PLAN) and two control classes who were taught the conventional method by two different teachers. These four classes were given similar pretests and post tests of Researcher-made reading test, Center for Educational Measurement's (CEM) Standardized Reading Test, self-efficacy inventory, Mokhtari and Reichard's (2002) Metacognitive Awareness of Reading Strategies Inventory (MARSI), and Rhody and Estill's (1980) Rhody Secondary Reading Attitude Assessment (RSRAA). Results of the study reveal that there is a significant difference in the reading performance of selected freshman high school students before and after the teaching of metacognitive strategies only in researcher-made reading test. However, no significant difference was noted in the metacognitive awareness, reading performance from CEM Standardized Reading results, reading motivation and self-efficacy of selected freshman high school students. There is no significant difference in the metacognitive awareness, reading motivation and self-efficacy of freshman high school students who were explicitly taught metacognitive strategies, and those who underwent the regular literature program. The results of the researcher-made reading test revealed that the experimenta groups performed better compared with the control groups. However, the CEM Standardized Reading test revealed opposite findings, the control groups performed significantly better than the experimental groups. Students' journals reflect their metacognitive awareness and their use of efferent stance while reading and responding to texts. The respondents only utilize both efferent and aesthetic stances only in texts that are close to their experiences. There is a significant relationship between reading performance and self-efficacy in experimental classes while a significant relationship was noted between reading performance and reading motivation in control classes.